Pengaruh Agile Leadership, Beban Kerja, dan Kepuasan Kerja Terhadap Kinerja Karyawan - Febrisi Dwita; Deni Surapto (Economy Deposit Journal (E-DJ), 2022)
The Open University (UT) is a higher education institution that has conducted distance learning since 1984. To facilitate its services, UT has a Distance Learning Program Unit (UPBJJ) which is a UT technical implementation unit spread across every province. The functions and duties of UPBJJ-UT are as a place for students to carry out academic administrative and academic activities. For daily activities, UPBJJ-UT has the task of carrying out administrative and public relations activities as well as promotions, carrying out learning assistance services and teaching materials services which include tutorials and extracurricular activities, and developing, fostering, and implementing collaboration with various agencies. This requires the optimal performance of human resources in order to be able to compete against its competitors. Agile can be understood as the ability to react appropriately and quickly to emerging changes, as well as the ability to survive in volatile market conditions. The population and sample in this study are UT employees and leaders who are in regional units in each province with a sample of 200 people, for leaders starting from the Director, four people at the manager level. The analytical tool used with SMART PLS and description analysis with SPSS. The results showed that there was a positive influence of agile leadership and work stress on employee performance, and the results of the analysis test on job satisfaction on employee performance.